The family of bacterial ADP-ribosylating exotoxins. - Krueger, K M (1995)
Pathogenic bacteria utilize a variety of virulence factors that contribute to the clinical manifestation of their pathogenesis. Bacterial ADP-ribosylating exotoxins (bAREs) represent one family of virulence factors that exert their toxic effects by transferring the ADP-ribose moiety of NAD onto specific eucaryotic target proteins. The observations that some bAREs ADP-ribosylate eucaryotic proteins that regulate signal transduction, like the heterotrimeric GTP-binding proteins and the low-molecular-weight GTP-binding proteins, has extended interest in bAREs beyond the bacteriology laboratory. Molecular studies have shown that bAREs possess little primary amino acid homology and have diverse quaternary structure-function organization. Underlying this apparent diversity, biochemical and crystallographic studies have shown that several bAREs have conserved active-site structures and possess a conserved glutamic acid within their active sites.